Strategi Merencanakan dan Memilih Perguruan Tinggi Bagi Anak-Anak Tamatan SLTA di Desa bawonohono, kec. Fanayama, Nias Selatan - Togu Harlen Lbn. Raja; Edward A. Lbn. Raja; HD. Melva Sitanggang (Akademi Farmasi YPPM Mandiri, 2022)
Basically, every high school graduate will continue their education to higher education level either at universities, institutes, colleges, polytechnics and academies. Therefore, it is very important for graduates to make plans to continue their education, by getting information about the colleges that will be chosen by graduates so that they are not wrong in making decisions to continue their education, with good planning, graduates will get a future which is also good, because the graduates have made good decisions in continuing their education to the tertiary level. Every child must have ideals about his future, where these ideals become the vision and mission of his life which will be obtained with the help of education. Currently, high school graduates do not really understand how to choose a major in lectures, so many graduates are less successful in their education and less successful in finding work. This service program is carried out using the lecture/socialization method, with the aim that graduates and parents can choose the right college. Based on the results of the service program in the field, it can be explained that the service program can run successfully where only 15% of participants do not understand and do not understand this service program and 85% understand and understand this service program very well.